Probing the Antecedents of Iranian EFL Teachers’ Motivation and Demotivation - Ghanizadeh, Afsaneh; Erfanian, Javad (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
Teachers play the focal roles in the lives and learning of the students in their classrooms. They indeed serve many roles including, teaching knowledge to students, mentoring and nurturing students, becoming role models, and creating a friendly and facilitative learning environment. These encompassing roles underscore teachers’ motivational disposition. The present article reports on a qualitative study exploring Iranian EFL teachers’ motivating and demotivating factors. To do so, semi-structured interviews with 9 high school EFL teachers were conducted. The analysis of the interview protocols yielded a number of motivating and demotivating factors. These factors were categorized under three antecedents for motivation and three for demotivation. It was concluded that: a) most of the teachers were dissatisfied with students’ inattention and inapt conduct of school officials or authorities; b) some were dissatisfied with payment and time restrictions; c) in the other hand, most of them were satisfied with students’ enthusiasm; and d) some of them were satisfied with parents’ appreciation.